Forced folds and fractures - Cosgrove, J. W.; Ameen, Mohammed S. (Geological Society special publication, 2000)
This detailed study of forced folds generated in a variety of situations focuses on the geometry and spatial organisation of these folds and their associated fracture patters. A comparison is made between forced folds and buckle folds.